Extirpated prairie species demonstrate more variable phenological responses to warming than extant congeners. Issue 6 (16th June 2021) - Zettlemoyer, Meredith A.; Renaldi, Katarina; Muzyka, Michael D.; Lau, Jennifer A.
Abstract : PREMISE: Shifting phenology in response to climate is one mechanism that can promote population persistence and geographic spread; therefore, species with limited ability to phenologically track changing environmental conditions may be more susceptible to population declines. Alternatively, apparently nonresponding species may demonstrate divergent responses to multiple environmental conditions experienced across seasons. METHODS: Capitalizing on herbarium records from across the midwestern United States and on detailed botanical surveys documenting local extinctions over the past century, we investigated whether extirpated and extant taxa differ in their phenological responses to temperature and precipitation during winter and spring (during flowering and the growing season before flowering) or in the magnitude of their flowering time shift over the past century. RESULTS: Although warmer temperatures across seasons advanced flowering, extirpated and extant species differed in the magnitude of their phenological responses to winter and spring warming. Extirpated species demonstrated inconsistent phenological responses to warmer spring temperatures, whereas extant species consistently advanced flowering in response to warmer spring temperatures. In contrast, extirpated species advanced flowering more than extant species in response to warmer winter temperatures. Greater spring precipitation tended to delay flowering for both extirpated and extant taxa. Finally, both extirpated and extant taxa delayed flowering over time. CONCLUSIONS: This study highlights the importance of understanding phenological responses to seasonal warming and indicates that extirpated species may demonstrate more variable phenological responses to temperature than extant congeners, a finding consistent with the hypothesis that appropriate phenological responses may reduce species' likelihood of extinction.